2020
DOI: 10.1021/acs.orglett.0c00154
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Enantioenriched α-Deuterated α-Amino Acids Enabled by an Organophotocatalytic Radical Approach

Abstract: A mild, versatile organophotoredox protocol has been developed for the preparation of diverse, enantioenriched α-deuterated α-amino acids. Distinct from the well-established two-electron transformations, this radical-based strategy offers the unrivaled capacity of the convergent unification of readily accessible feedstock carboxylic acids and a chiral methyleneoxazolidinone fragment and the simultaneous highly diastereo-, chemo-, and regioselective incorporation of deuterium. Furthermore, the approach has addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 77 publications
0
57
0
1
Order By: Relevance
“…Asymmetric synthesis of the α-deuterated α-AA derivatives 17 by addition of radicals generated from carboxylic acids by organophotoredox catalysis to a chiral substrate 1 b and the isolation of Leu-D (Wang, 2020). [106] Later, the Gómez-Suárez [107] and Schubert [105] groups independently demonstrated that the strategy reported by Wang et al [106] is general and perfectly fits Scheme 11. Asymmetric synthesis of the α-AA derivatives 18 by photocatalytic addition of radicals generated from carboxylic acids to a chiral substrate 1 b and the isolation of α-AA 19 a (Gómez-Suárez, 2020).…”
Section: Seebach-beckwith Alkene As a Chiral Substratementioning
confidence: 92%
See 3 more Smart Citations
“…Asymmetric synthesis of the α-deuterated α-AA derivatives 17 by addition of radicals generated from carboxylic acids by organophotoredox catalysis to a chiral substrate 1 b and the isolation of Leu-D (Wang, 2020). [106] Later, the Gómez-Suárez [107] and Schubert [105] groups independently demonstrated that the strategy reported by Wang et al [106] is general and perfectly fits Scheme 11. Asymmetric synthesis of the α-AA derivatives 18 by photocatalytic addition of radicals generated from carboxylic acids to a chiral substrate 1 b and the isolation of α-AA 19 a (Gómez-Suárez, 2020).…”
Section: Seebach-beckwith Alkene As a Chiral Substratementioning
confidence: 92%
“…Eco-friendly and green approaches were elaborated by applying readily accessible feedstock carboxylic acids and amines for straightforward radical coupling under mild conditions. [102,103,[105][106][107]166]…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the groups of Gómez‐Suárez, [71b] Wang, [71a] and Shubert [71c] independently reported a photoredox‐mediated decarboxylative synthesis of UAAs using 13 as a radical acceptor (Scheme 24). Whereas the procedure developed by Gómez‐Suárez and co‐workers presents a broad scope with a variety of aromatic and aliphatic α‐keto acids, as well as aliphatic carboxylic acids as radical precursors, [71b] the approach developed by Wang and co‐workers allows the synthesis of α‐deuterated UAAs, [71a] and the method developed by the Shubert group facilitates the modification of peptides under metal‐free conditions [71c] . All three methods allow the straightforward synthesis of a wide range of UAAs in good to excellent yields and high diastereoselectivities.…”
Section: Modificationsmentioning
confidence: 99%